The Negative Impact of Triptolide on the Immune Function of Human Natural Killer Cells - Na Wang; Xiaoyun Min; Ning Ma; Zhuoran Zhu; Bo Cao; Yuan Wang; Qing Yong; Jingjin Huang; Ke Li (MDPI AG, 2023)
Triptolide (TP), a bioactive compound extracted the from traditional Chinese medicine Tripterygium wilfordii Hook F (TwHF), has been shown to be effective in treating several autoimmune diseases, and has suppressive effects in several key immune cells such as dendritic cells, T cells, and macrophages. However, it is unknown whether TP has an impact on natural killer (NK) cells. Here, we report that TP has suppressive effects on human NK cell activity and effector functions. The suppressive effects were observed in human peripheral blood mononuclear cell cultures and purified NK cells from healthy donors, as well as in purified NK cells from patients with rheumatoid arthritis. TP treatment induced downregulation of NK-activating receptor (CD54, CD69) expression and IFN-gamma secretion, in a dose-dependent manner. When exposed to K562 target cells, TP treatment induced inhibition of surface expression of CD107a and IFN-gamma synthesis in NK cells. Furthermore, TP treatment induced activation of inhibitory signaling (SHIP, JNK) and inhibition of MAPK signaling (p38). Thus, our findings demonstrate a previously unknown role for TP in NK cell functional suppression and reveal several key intracellular signaling that can be regulated by TP. Our findings also offer new insight into mechanisms of TP therapeutic treatment in autoimmune disease.